2021
DOI: 10.1175/jcli-d-21-0165.1
|View full text |Cite
|
Sign up to set email alerts
|

Global trends in downward surface solar radiation from spatial interpolated ground observations during 1961-2019

Abstract: Downward surface solar radiation (SSR) is a crucial component of the Global Energy Balance, affecting temperature and the hydrological cycle profoundly, and it provides crucial information about climate change. Many studies have examined SSR trends, however they are often concentrated on specific regions due to limited spatial coverage of ground based observation stations. To overcome this spatial limitation, this study performs a spatial interpolation based on a machine learning method, Random Forest, to inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 57 publications
3
6
0
Order By: Relevance
“…The annual average anomaly variations in regions and globally show that Asia, Africa, Europe and North America are the four contributors to the global dimming, while Europe and North America are two major contributors to the brightening. This is in general agreement with the results obtained by previous machine learning (Yuan et al, 2021). In addition, the discrepancy between the SSRIH 20CR and SSRIH grid is more significant in low-coverage areas (right) than in high-coverage regions (left).…”
Section: Comparison Of the Spatial And Temporal Variation Characteris...supporting
confidence: 92%
See 1 more Smart Citation
“…The annual average anomaly variations in regions and globally show that Asia, Africa, Europe and North America are the four contributors to the global dimming, while Europe and North America are two major contributors to the brightening. This is in general agreement with the results obtained by previous machine learning (Yuan et al, 2021). In addition, the discrepancy between the SSRIH 20CR and SSRIH grid is more significant in low-coverage areas (right) than in high-coverage regions (left).…”
Section: Comparison Of the Spatial And Temporal Variation Characteris...supporting
confidence: 92%
“…Machine learning is increasingly being used in spatial interpolation, such as the spatial reconstruction of surface temperature datasets (Huang et al, 2022;Kadow et al, 2020) or the spatial and temporal reconstruction of turbulence resolution (Fukami et al, 2021). Furthermore, it shows high accuracy and low uncertainty in reproducing and predicting SSR (Leirvik and Yuan, 2021;Tang et al, 2016;Yuan et al, 2021). However, long-term homogenized SSR datasets with global terrestrial coverage have yet to be developed, resulting in significant uncertainties in assessing global SSR variation (Jiao et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Cutforth and Judiesch (2007) document dimming in Canada from 1958 to the 1990s. Using a machine learning method to map surface solar radiation observations over the globe, Yuan et al (2021) show brightening from 1982 through 2019 in central and eastern Canada, Mexico, and the Great Plains of the U.S. He et al (2018) show that dimming from 1952 to 1980 was widespread over all of China, however, from 1994 to 2010 brightening was confined to the southern half of the country, while dimming occurred in the North China Plain.…”
Section: Association Of Multidecadal Nh Sst Variations To Continental...mentioning
confidence: 99%
“…Using a machine learning method to map surface solar radiation observations over the globe, Yuan et al. (2021) show brightening from 1982 through 2019 in central and eastern Canada, Mexico, and the Great Plains of the U.S. He et al.…”
Section: Connection Of Ssts To Continental Brightening and Dimmingmentioning
confidence: 99%
“…Long-and short-term climatic trends include changes in the distribution of temperature, precipitation, and cloudiness. Observational studies have found that temperature increases over time, with an increase in all regions on Earth and with an increase in the level, variability, and drivers of the level of temperature; see, for example, Storelvmo et al (2016), Yuan et al (2021), and Kotz et al (2021).…”
Section: Introductionmentioning
confidence: 99%